2010
DOI: 10.1303/aez.2010.275
|View full text |Cite
|
Sign up to set email alerts
|

Point mutations in domain II of the voltage-gated sodium channel gene in deltamethrin-resistant Aedes aegypti (Diptera: Culicidae)

Abstract: The continuous usage of pyrethroids against insects has provoked the emergence of insecticide resistance that has become a major obstacle to disease vector control. The knockdown resistance (kdr) voltage-gated sodium channel gene is regarded as a key to understanding the mechanism of resistance to pyrethroids. The main purpose of this study is to identify point mutations in the sodium channel gene associated with deltamethrin resistance in Aedes aegypti. Two mutations in the IIS6 domain of the channel, S989P a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 23 publications
(32 reference statements)
7
93
3
1
Order By: Relevance
“…The S989P mutation has always been linked to the V1016G mutation; however, V1016G has sometimes been found in the absence of S989P [12]. The observed co-occurrence of the V1016G and S989P mutations with high frequency in Myanmar correspond to the former scenario.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The S989P mutation has always been linked to the V1016G mutation; however, V1016G has sometimes been found in the absence of S989P [12]. The observed co-occurrence of the V1016G and S989P mutations with high frequency in Myanmar correspond to the former scenario.…”
Section: Discussionmentioning
confidence: 86%
“…The observed co-occurrence of the V1016G and S989P mutations with high frequency in Myanmar correspond to the former scenario. Srisawat et al indicated that the co-occurrence of V1016G and S989P enhanced the resistance of Aedes aegypti to deltamethrin [12]. However, the authors were unable to determine the effect of the single S989P mutation on pyrethroid sensitivity, and were therefore unable to provide direct evidence of how the two mutations were associated with resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, an F1534C substitution in IIIS6 was discovered in DDT/permethrin-resistant Aedes aegypti in Thailand and Vietnam [33,34,35,36]. Furthermore, two additional mutations, S989P and D1763Y, were found to coexist with V1016G in permethrin-resistant populations in Thailand [37,38,39] and in Taiwan [40], respectively.…”
Section: Identification Of Single Nucleotide Polymorphisms (Snps) mentioning
confidence: 99%
“…Similarly, nucleotide sequence polymorphisms in the sodium channel gene from geographically distinct populations potentially influence the contribution of kdr mutations to pyrethroid resistance. For example, the S989P mutation appears to synergize the effects of the V1016G mutation based on analysis of field populations in Thailand [37]. However, genetic addition of the S989P allele in either the homozygous or heterozygous form to V1016G homozygotes did not enhance resistance to permethrin or deltamethrin in another study in Indonesia [45].…”
Section: Functional Conformation Of Kdr Mutations In Xenopus Oocytesmentioning
confidence: 99%